TOWARD IMPROVEMENT OF VO2Max BOXING SHADOW BOXING - Susanti Ngoalo; Nurhayati Liputo; Edy Dharma Putra Duhe (Jambura Journal of Sports Coaching, 2020)
The purpose of this study was to determine how much influence the Shadow Boxing exercise had on increasing VO2Max in boxing. The method used in this research is experiment. The design used is a One group Pre-test-post test design. The sample of this research was conducted on sixth semester students of Sport Coaching Education, amounting to seven students. Based on the results of the study, the average increase in maximum aerobic endurance capacity or VO2Max is before being given Shadow Boxing training by 24.3 and after being given Shadow Boxing training by 31.78. This proves that the Shadow Boxing exercise gives positive impact on VO2Max. hence, this exercise can be recommended to be added as a special portion of the exercise menu for boxers who have problems with poor aerobic capacity.